AndroidTrack: An Investigation of Using Social Networks’ Applications in Android Platforms - Mostfa, Ahmed A.; Abdulahad, Fedaa Noeel; Sharkawy, Abdel-Nasser (Iraqi Journal of Science, 2021)
In this paper, time spent and the repetition of using the Social Network Sites (SNS) in Android applications are investigated. In this approach, we seek to raise the awareness and limit, but not eliminate the repeated uses of SNS, by introducing AndroidTrack. This AndroidTrack is an android application that was designed to monitor and apply valid experimental studies in order to improve the impacts of social media on Iraqi users. Data generated from the app were aggregated and updated periodically at Google Firebase Real-time Database. The statistical factor analysis (FA) was presented as a result of the user’s interactions.